(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article provides a scientific and theoretical analysis of the relationship between national interests and global challenges. In the context of globalization, addressing universal issues such as climate change, security, migration, environmental protection, and sustainable development while safeguarding national interests has become increasingly important. The article examines the concept of national interests, the nature of global challenges, and the role of international cooperation and balanced policy approaches in addressing them.